Influence of physical activity on the values of hemorheological parameters - Anna Szpernalowska; Anna Marcinkowska-Gapińska (Nicolaus Copernicus University in Toruń, 2024)
Physical activity is a major factor contributing to maintaining overall health and properly functioning circulatory system. One of the underlying mechanisms is modifying blood flow by influencing hemorheological parameters, the most important of which are: hematocrit, plasma viscosity, whole blood viscosity, the ability of red blood cells to aggregate, deform and orient. We conducted a literature review to investigate how different types, intensities and phases of physical activity affect rheological properties of blood. The results show that short-term effects of exercise differ from the long-term consequences and rheology of blood varies depending on strength/endurance type of the training as good as on its regularity and intensity. Findings from this research may be applicable in improving sport's performance and health maintenance in athletes.